Various MRI Findings of Spinal Ependymoma - Yoon Joo Shin; Eugene Lee; Joon Woo Lee; Yusuhn Kang; Seung-Jae Hyun; Ki-Jeong Kim; Tae-Ahn Jahng; Hyun-Jib Kim; Heung Sik Kang (대한영상의학회지, 2017)
Purpose To present the typical and atypical magnetic resonance image (MRI) findings of intramedullary spinal ependymomas, and compare these findings with pathological subtypes.